recursion - I want to solve the recurrence relation F(n,m) = F(n-1,m) + F(n,m-1) + 1? -


I want to know how to solve repetition in 2 variables I want to solve the following link:

  F (n, m) = f (n -1, m) + f (n, m -1) + 1   

initial conditions:

  F (m, 0) = m f (0, n) = nf (0,0) = 0    

  F (n, m) {if (n == 0) & amp; Amp; Amp; Amp; Amp; Amp; & Amp; Amp; (M == 0) return 0 and if (n == 0) returns M and return (M == 0) back and other return F (N -1, m) + F (N, M-1) + 1 }  / pre>  

Comments

Popular posts from this blog

Pass DB Connection parameters to a Kettle a.k.a PDI table Input step dynamically from Excel -

multithreading - PhantomJS-Node in a for Loop -

c++ - MATLAB .m file to .mex file using Matlab Compiler -